A methodological approach for the synthesis of 4-aryl-8-arylidene-2-cyanoimino-1, 2, 3, 4, 5, 6, 7, 8-octahydroquinazolines. Issue 8 (18th April 2022) - Moustafa, Amr H.; Hussein, Bahgat R. M.
Abstract: An efficient methodological approach for the synthesis of a novel series of 4-aryl-8-arylidene-2-cyanoimino-1, 2, 3, 4, 5, 6, 7, 8-octahydroquinazolines (aryl-CIOHQs) was presented via one-pot four-component reaction of cyclohexanone, two-folds of various aromatic aldehydes and cyanoguanidine in the presence of sodium ethoxide as basic catalyst. The same target products (aryl-CIOHQs) were also reproduced in good yields using an ordinary method via two-component reaction of 2, 6-diarylidinecyclohexanone derivatives with cyanoguanidine in the same condition. Graphical Abstract: UF0001